Minds and Machines : A Conversation with Miguel Nicolelis. - Burton, Howard (Open Agenda Publishing, 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Miguel Nicolelis, Professor of Neurobiology, Neurology, Neurosurgery, Biomedical Engineering, Psychology and Neuroscience and Orthopaedic Surgery and Co-Director of the Center for Neuroengineering at Duke University. This thought-provoking conversation dives into Miguel Nicolelis' extensive and important research for over 20 years now and how he has been blurring the line between science fiction and science fact, developing increasingly sophisticated ways of harnessing the thoughts of rats, monkeys and humans to dr.
Description based upon print version of record.
Keywords: Nicolelis, Miguel A. L. -- Interviews.; Nicolelis, Miguel A. L.; Brain-computer interfaces.; Interfaces cerveau-ordinateur.; Neurosurgery.; Surgery.; MEDICAL.; Neuropsychology.; PSYCHOLOGY.; Biomedical.; TECHNOLOGY & ENGINEERING.; Brain-computer interfaces; Interviews